A cross-sectional study of children's temperament, food consumption and the role of food-related parenting practices. (1st July 2019) - Kaukonen, Riikka; Lehto, Elviira; Ray, Carola; Vepsäläinen, Henna; Nissinen, Kaija; Korkalo, Liisa; Koivusilta, Leena; Sajaniemi, Nina; Erkkola, Maijaliisa; Roos, Eva
Abstract: Although evidence exists of the association between children's temperament and weight, only few studies have examined how temperament is associated with actual food consumption among preschoolers. We examined concurrent associations between children's temperament and the consumption of different foods, and investigated whether the association between children's temperament and vegetable consumption is mediated by vegetable-related parenting practices. We utilized the data from the cross-sectional DAGIS study of 864 preschool children aged between three to six and their families, conducted between 2015 and 2016 in Finland. The parents reported their children's temperament, food consumption, and their vegetable-related parenting practices. Adjusted logistic regression analyses found positive associations between surgency and vegetable consumption as well as between effortful control and vegetable consumption. Both associations were mediated by one examined vegetable-related parenting practice: enhanced availability and autonomy support. No associations were found between children's negative affectivity and food consumption or vegetable-related parenting practices. In conclusion, children's temperament may be an important factor behind food-related parenting practices and children's diet. However, further longitudinal research and research covering different food-related parenting practices and home environment factors is necessary to better understand the complex associations between temperament and food consumption among young children.